Wealth and happiness across the world Material prosperity predicts life evaluation, whereas psychological prosperity predicts positive feeling.[article]. - Diener, Ed
The Gallup World Poll, the first representative sample of planet Earth, was used to explore the reasons why happiness is associated with higher income, including the meeting basics needs, fulfillment of psychological needs, increasing satisfaction with one's standard of living, and public goods. Across the globe, the association of log income with subjective well-being was linear but convex with raw income, indicating the declining marginal effects of income on subjective well-being. Income was a moderately strong predictor of life evaluation but a much weaker predictive of positive and negative feelings. Possessing luxury conveniences. In contrast, feeling were most associated with the fulfillment of psychological needs: learning, autonomy, using ones' skills, respect, and the ability to count on others in an emergency, Thus, two separate types of prosperity- economic and social psychologiccal-best predict different types of well-being. -- (from the author)
Keywords: Income; Subjective well-being.; Money; Wealth; Happiness